2013
DOI: 10.1016/j.conbuildmat.2013.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Optimising low acoustic impedance back-fill material wave barrier dimensions to shield structures from ground borne high speed rail vibrations

Abstract: Ground borne vibrations generated due to high speed train passage can cause undesirable effects on the nearby environment. One approach to mitigate vibration levels is to use "wave barriers", however their installation cost may be very high. In an attempt to minimize construction costs, numerical modelling and physical experiments are performed to determine guidelines for the optimisation of trench dimensions. Substantial savings are found to be achievable through carefully chosen barrier dimensions. Firstly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(48 citation statements)
references
References 31 publications
2
46
0
Order By: Relevance
“…16, it is clear that it is the stiffness of the layer that is the dominant parameter, not its impedance as suggested by Massarsch [14] and used by other authors, e.g. [16,40]. In particular, materials B and E (see Table 5) have the same impedance but different insertion loss.…”
Section: Effect Of Barrier Materials Propertiesmentioning
confidence: 55%
See 1 more Smart Citation
“…16, it is clear that it is the stiffness of the layer that is the dominant parameter, not its impedance as suggested by Massarsch [14] and used by other authors, e.g. [16,40]. In particular, materials B and E (see Table 5) have the same impedance but different insertion loss.…”
Section: Effect Of Barrier Materials Propertiesmentioning
confidence: 55%
“…Connolly et al [40] used a 3D FE model to study the effects of an open trench adjacent to a railway line. It was shown that the depth is important but the width is not.…”
mentioning
confidence: 99%
“…reason many parametric studies have been performed [5][6][7][8]. Since most of the vibration energy generated by the train transit is transmitted by Rayleigh waves, all parameters are normalized with respect to soil Rayleigh wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…Notice that the location of excitation may differ between equations (1) and (3). An accurate prediction of these vibrations can be performed by several numerical models, for high-speed trains [26][27][28] or for urban networks [29][30][31]. However, a significant computation time is needed for a complete vehicle/track/soil simulation and a vast section of vehicle, track and soil parameters are necessary.…”
Section: Problem Statementmentioning
confidence: 99%